Nitrogênio e água como fatores de produtividade da soja (Glycine max (L.) Merrill) - Barzotto, Flávia (2015)
Soy is one of the most important agricultural products in the world and in Brazil, which is the second largest producer of culture. Due to the excellent combination of productivity, protein and oil content in grain, this culture has great agronomic interest. The supplemental irrigation and nitrogen fertilization during the development of soybean featuring ways to increase productivity and reduce the risks associated with drought. This study aims to evaluate the yield of soybean as the blades effect of irrigation and nitrogen fertilization on the Eastern Plateau Region of Rio Grande do Sul. The work was conducted in the city of Ibirubá in Agricultural Guajuvira (28 ° 28'19,31 "S and 53º11'17,40" O), using the soybean cultivar BMX Active, and irrigation management was carried out according to evapotranspiration particular culture through the Class A pan installed near the area of the experiment . The design was a randomized block design with four replications in a factorial scheme with split plot. In the main plots were implanted irrigation related treatments (345.5; 432.3; 525.8; 568.1; 594.7 mm) and the sub-plots treatments related to nitrogen fertilization rates (0, 40 , 80, 100 and 120 kg N ha-1) using as source urea 46% nitrogen (N) in a single application in the R1 stage (early flowering). During the growing period, were evaluated some variables including plant height (AP), stem diameter (DC), the aboveground part of the plant (SDM) and the leaf area index (LAI). We also evaluated the crop yield components were: number of vegetable per plant (NLP), thousand grain weight (MMG) and grain yield (GY). Besides these, were evaluated at R2 stage of development of culture, the lump of dry matter (MSN) and number of nodes (NN) in soybean plants for the blade 568.1 mm and the doses 0, 40, 80 and 120 kg ha-1 of N. it can be concluded that the cultivar Active BMX, for Ibirubá RS region is dependent on water depth use. Irrigation management (120% ETc) may be indicated when maximum grain yield objective. The variables analyzed (AP, MSPA and IAF) were influenced by irrigation and only MMG production component was positively influenced by nitrogen fertilization. Nitrogen fertilization, regardless of the dose used was not a positive factor for the soybean grain yield of addition and is proven that soybean nodulation, the cultivar studied is affected by the application of nitrogen fertilizer.